Recent conjugation strategies of small organic fluorophores and ligands for cancer-specific bioimaging. (25th March 2016) - Ha, Yonghwang; Choi, Hyun-Kyung
Abstract: Conjugation between various small fluorophores and specific ligands has become one of the main strategies for bioimaging in disease diagnosis, medicinal chemistry, immunology, and fluorescence-guided surgery, etc. Herein, we present our review of recent studies relating to molecular fluorescent imaging techniques for various cancers in cell-based and animal-based models. Various organic fluorophores, especially near-infrared (NIR) probes, have been employed with specific ligands. Types of ligands used were small molecules, peptides, antibodies, and aptamers; each has specific affinities for cellular receptor proteins, cancer-specific antigens, enzymes, and nucleic acids. This review can aid in the selection of cancer-specific ligands and fluorophores, and may inspire the further development of new conjugation strategies in various cellular and animal models. Graphical abstract: Highlights: Examination of molecular fluorescent techniques for monitoring various cancers. Investigation of various organic/organometallic fluorophores probes, especially NIR probes. Reviews of various types of specific ligands for targeting of cancer cells/tissues. Reviews of cancer-specific cellular targets in various cancers.